Alleviating effects of pea peptide on oxidative stress injury induced by lead in PC12 cells via Keap1/Nrf2/TXNIP signaling pathway - Li, Ning; Wen, Liuding; Wang, Fangyu; Li, Tiange; Zheng, Haodan; Wang, Tianlin; Qiao, Mingwu; Huang, Xianqing; Song, Lianjun; Bukyei, Erkigul; Li, Mingming (Frontiers in Nutrition, 2022)
Background Lead poisoning causes an oxidative stress response – a key “bridge” connecting various pathways – in the human body. Oxidative stress usually implies an imbalance between pro-oxidants and antioxidants. Moreover, Nrf2, Keap1, and TXNIP proteins play an essential role in oxidative stress. Some studies showed that pea peptides could alleviate the oxidative stress response. However, the effect and mechanism of pea peptide on oxidative stress response induced by lead in PC12 cells has not been reported. Aim Investigating the effect and mechanism of pea peptides in alleviating oxidative damage in PC12 cells induced by lead. Methods In this study, cell viability was measured by CCK8 (Cell Counting Kit-8). Superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), glutathione reductase (GR), glutathione peroxidase (GPx), reactive oxygen species (ROS), and lipid peroxidation (MDA) were measured using the corresponding Biochemical kits. The Keap1, Nrf2, and TXNIP protein expressions were tested using Western blot. Results Pea peptides PP3, PP4, and PP6 could reverse the decrease of cell viability caused by lead exposure (P < 0.05), the elevation of ROS and MDA caused by lead exposure, and the decrease of CAT, SOD, GR, GPx, and GSH/GSSG caused by lead exposure (P < 0.05). Moreover, PP3, PP4, and PP6 could reduce the elevated expression of Keap1 and TXNIP caused by lead exposure; and increase the expression of Nrf2 (P < 0.05). Conclusion PP3, PP4, and PP6 can alleviate lead-induced oxidative stress damage in PC12 cells, and the Nrf2/Keap1/TXNIP signaling pathway may play an essential role in this process.